Can ChatGPT be used as an education assistant in the field of health sciences? Examining with the integration of meta-analysis and co-citation analysis - Emrah Gökay Özgür; Nural Bekiroğlu (Heliyon)
Background: Meta-analysis studies are frequently included in the literature, but studies integrated with co-citation analysis are very few. There is no study that evaluates the success of ChatGPT in the field of health sciences, especially by integrating these two methods. Objective: This study aims to reveal whether ChatGPT can be used as an educational assistant by comparing the performance of students in exams in the field of health sciences with ChatGPT through the integration of meta-analysis and co-citation analysis. Methods: We searched Web of Science for articles until May 2024. The studies comparing students' exam performances with ChatGPT 3.5 and 4.0 versions in the field of health sciences were included in the meta-analysis. Co-citation analysis was performed for the references of the studies included in the meta-analysis and the relationship between the studies and the references was examined. Results: It is seen that the exam performance of the students is better than ChatGPT 3.5 (OR = 3.173, 95 % CI (1.132–8.869). In the co-citation analysis, three clusters were obtained. It is seen that the exam performances of ChatGPT 4.0 are better than the students (OR = 2.589, 95 % CI (1.046–6.409). In the co-citation analysis obtained with the references of these four studies, two clusters were identified. The most cited studies, namely Kung et al., Aidan et al., and Hopkins et al., intersect in one cluster. Conclusion: The results obtained with the integration of meta-analysis and co-citation analysis are agree with the literature for both ChatGPT 3.5 and ChatGPT 4.0. In general, using co-citation analysis and meta-analysis together, increases the depth and scope of the analysis. The results obtained in these analyzes also show that the use of ChatGPT as an educational assistant in the field of health sciences is increasing day by day.